PERTUMBUHAN DAN HASIL 4 VARIETAS KEDELAI TOLERAN KEKERINGAN DENGAN BERBAGAI DOSIS MIKORIZA PADA LAHAN MARJINAL - Riduan, Ahmad; Nusifera, Sosiawan; Buhaira, Buhaira; Salim, Helmi; Zikin, Ahmad Nurro (Jurnal Agroecotania : Publikasi Nasional Ilmu Budidaya Pertanian, 2025)
ABSTRACT Soybean (Glycine max L.) is one of the most important food crops in Indonesia after rice and corn. Soybeans are rich in plant-based protein, making them an excellent choice for improving community nutrition due to their health benefits. However, soybean production in Indonesia, including in Jambi Province, still faces many challenges, one of which is the predominance of marginal land, mainly ultisol soils. Therefore, improvements in cultivation techniques are necessary to address these problems. Selecting superior varieties and using biofertilizers such as Arbuscular Mycorrhizal Fungi (AMF) are potential solutions to enhance soybean productivity. This study aims to determine the different responses of soybean varieties to various mycorrhizal doses and to identify the optimal mycorrhizal dose for each variety. The research was conducted at the Teaching and Research Farm of the Faculty of Agriculture, University of Jambi, located in Mendalo Darat Village, Muaro Jambi Regency. Experimental study arranged in a Randomized Complete Block Design (RCBD) with a two-factor factorial pattern. The first factor was the soybean variety, consisting of four varieties: Argomulyo, Dena-1, Dering-2, and Dering-3. The second factor was mycorrhizal application, consisting of three levels: no mycorrhiza, 10 g/plant, and 20 g/plant. The observed variables included plant height, total leaf area, flowering age, infection rate, harvest age, number of pods per plant, number of filled pods, weight of 100 seeds, seed weight per plant, and yield per hectare. Prior to data analysis, normality was tested using the Shapiro-Wilk test. Data that met the normality requirement were then statistically analyzed using analysis of variance (ANOVA), and if significant differences were found, further testing was conducted using the Least Significant Difference (LSD) test at the 5% significance level (α = 5%). The results showed different responses among soybean varieties to various mycorrhizal doses, particularly in yield per hectare. There were significant effects of the single factors variety and mycorrhizal doses on variables such as plant height, leaf area, flowering age, harvest age, number of pods per plant, number of filled pods, weight of 100 seeds, and seed weight per plant. However, for the infection rate variable, a significant effect was only found for the mycorrhizal factor, not for the variety factor. A mycorrhizal doses of 20 g/plant gave the best results for Argomulyo, Dering-2, and Dering-3 varieties in terms of total leaf area, infection rate, number of pods per plant, number of filled pods, seed weight per plant, and yield per hectare. Meanwhile, for the Dena-1 variety, the optimal result in yield per hectare was obtained with 10 g/plant of mycorrhiza. Keywords: Soybean Varieties, Mycorrhiza doses, Plant growth and Yield